(3eYLe eG ESJYLes - (3CHh YHjO GdHcQjs
(3ChdgG (B:s
(3jHOC HcJGH MQa GdRGi(B( (3GdRGi hGdCda (B) s
(3BNQgG (B:s
(3hai JYQjHgG hLhg bO JbOe PcQgG Je LejY GdcJGH GdeSei eYLe eG ESJYLe HMeO Gddg hYhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1737s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs